2015
DOI: 10.1007/s12020-015-0584-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of patients with gastric neuroendocrine neoplasms associated with chronic atrophic gastritis: a retrospective, multicentre study

Abstract: To provide data regarding clinical presentation, pathological features, management, and response to different treatments of patients with type I gastric neuroendocrine tumors in stages 0-2A. The study design consist of an Italian multicentre, retrospective analysis of patients with type I gastric neuroendocrine tumors managed with different therapeutic approaches: surgery, endoscopic surveillance, endoscopic resection, or somatostatin analog therapy. Among the 97 patients included, 3 underwent surgery, 45 (46.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
2
38
1
3
Order By: Relevance
“…In our type I NETs, G2 failed to be associated with gastric wall invasion or metastases, despite the fact that an association of grade with tumor behavior as well as patient outcome was ascertained for type III gastric NETs, as well as for pancreatic and duodenal NETs [39-41]. These results bring the attention to previous type I NET series where G2 failed to predict tumor behavior [27, 42] or showed no apparent impact on tumor behavior and patient survival despite a high G2 type I NET percentage (71% reported by Lee et al [29] and 34% by Campana et al [43]).…”
Section: Discussionmentioning
confidence: 79%
“…In our type I NETs, G2 failed to be associated with gastric wall invasion or metastases, despite the fact that an association of grade with tumor behavior as well as patient outcome was ascertained for type III gastric NETs, as well as for pancreatic and duodenal NETs [39-41]. These results bring the attention to previous type I NET series where G2 failed to predict tumor behavior [27, 42] or showed no apparent impact on tumor behavior and patient survival despite a high G2 type I NET percentage (71% reported by Lee et al [29] and 34% by Campana et al [43]).…”
Section: Discussionmentioning
confidence: 79%
“…Somatostatin analogues reduce hypergastrinemia and have a direct antiproliferative effect on ECL cells. Although SSA are not yet recommended for types 1 and 2 GNETs, several case reports or cohort studies have reported reduction or disappearance of tumours treated with SSA (25,26,29,30). Even if SSA are considered as an over-treatment for types 1 and 2 GNETs, it is admitted that for selected cases SSA can be used, especially when endoscopic management is not feasible or not accepted by patients (31).…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Limited studies, including a few small prospective studies, have demonstrated regression or complete disappearance of tumors and marked decrease in serum gastrin, lasting up to several years. [30][31][32][33][34][35][36][37][38][39] SSAs (e.g. octreotide and lanreotide) can be considered in cases in which endoscopic resection is not feasible due to extensive multifocal disease, or submucosal/lymph node involvement, as well as recurrent disease after repeated endoscopic resection.…”
Section: Medical Managementmentioning
confidence: 99%